Gingival fenestration management: A rarefied case entity and literature review - Prem B Rajula M; Kalaivani Varatharajan; Rekha Mani; Shobana Krishnakumar (Wolters Kluwer Medknow Publications, 2020)
Dehiscence and fenestration are commonly confronted alveolar defects. But the combined mucosal and alveolar fenestration is uncommonly reported in the literature as they less often cause pain, and in majority of the cases, only aesthetic complaint is present. This article highlights the case report of a 28-year-old female patient who presented with aesthetic concern about gingival/mucosal fenestration in her right lower central incisor. She had a history of surgical endodontic treatment in the same tooth. In this case, mucosal fenestration was treated with regenerative therapy using bioactive glass with platelet-rich fibrin and free connective tissue graft. The treatment resulted in excellent aesthetic outcome and satisfactory bone healing.